2003
DOI: 10.1002/ajh.10451
|View full text |Cite
|
Sign up to set email alerts
|

Risk of bleeding complications with antiplatelet agents: Meta‐analysis of 338,191 patients enrolled in 50 randomized controlled trials

Abstract: Antiplatelet therapy has been the focus of extensive clinical investigations over the last two decades. A variety of agents and regimens have been advanced for the prevention and treatment of vascular disease. Despite the proven life-saving clinical benefits of inhibiting platelets, this therapy is associated with an increased risk of bleeding. The objective of this study was to determine the risk of hemorrhage in the major classes of antiplatelet agents. Data from clinical trials published 1988-2002 in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(106 citation statements)
references
References 51 publications
2
90
0
10
Order By: Relevance
“…Animal studies have shown that a new soluble form of the extracellular region of CD39 (solCD39) has systemic antithrombotic effects 30,31 ; however, antiplatelet therapy also tends to induce systemic bleeding. 2 This is an important limitation to clinical applicability and indicates a potential advantage of local gene transfer into injured vessels. Our study demonstrated that E-NTPDase expressed on SMCs inhibited platelet aggregation induced not only by ADP but also by collagen, although a high viral titer was required.…”
Section: Furukoji Et Al Placental E-ntpdase Suppresses Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have shown that a new soluble form of the extracellular region of CD39 (solCD39) has systemic antithrombotic effects 30,31 ; however, antiplatelet therapy also tends to induce systemic bleeding. 2 This is an important limitation to clinical applicability and indicates a potential advantage of local gene transfer into injured vessels. Our study demonstrated that E-NTPDase expressed on SMCs inhibited platelet aggregation induced not only by ADP but also by collagen, although a high viral titer was required.…”
Section: Furukoji Et Al Placental E-ntpdase Suppresses Thrombosismentioning
confidence: 99%
“…1 Although some of these agents effectively reduce cardiovascular events, 1 they can also produce systemic hemorrhagic side effects. 2 Platelet adhesion to injured vascular walls leads to platelet activation and the release of additional agonists such as ADP, serotonin, and thromboxane A 2 , which cause further platelet recruitment to injured sites. Because ADP plays a key role in platelet aggregation, 3 its metabolism in the blood is important in the regulation of platelet activation and recruitment.…”
mentioning
confidence: 99%
“…The potential benefit of higher aspirin doses preventing a cardiovascular event may be offset by an increased risk of bleeding. 32,33 Therefore, all-cause mortality was chosen as the primary outcome because it provides a balanced assessment of overall safety and effectiveness for any treatment option. 34 Given the likelihood of combining data from studies published in different decades and conducted in different countries, we also believed allcause mortality would provide a homogeneous outcome measure.…”
Section: Data Synthesismentioning
confidence: 99%
“…Although an examination of the risk of adverse events such as hemorrhagic stroke or gastrointestinal bleeding was beyond the scope of our study, this has been examined by others. 32,33 Pooling the rates of bleeding events reported in 31 33 and 50 32 randomized controlled trials showed that the rate of major bleeding events was similar for <100 mg compared to 100-325 mg aspirin daily; however, the rate of any bleeding events was significantly lower for <100 mg compared to 100-325 mg aspirin daily.…”
Section: Limitationsmentioning
confidence: 99%
“…Antithrombotic drugs, such as adenosine diphosphate (ADP) receptor blockers, acetylsalicylic acid (aspirin), and glycoprotein (GP) IIb/IIIa antagonists are used to prevent cardiovascular disease [2]. However, these drugs can have systemic hemorrhagic side effects [3,4]. Cancer is a very serious medical condition worldwide.…”
Section: Introductionmentioning
confidence: 99%